Performance analysis of DECK collective communication service - Silva, R.; Picinin, D.; Barreto, M.; Avila, R.; Diverio, T.; Navaux, P. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
Collective communication is very useful for parallel applications, especially those in which matrix and vector data structures need to be manipulated by a group of processes. We present a performance analysis of collective communication primitives designed for the DECK parallel programming environment, with the aid of different numerical methods used to solve hydrodynamics and mass transportation models.